Strategic Digital Communication for Empowering Online Communities: A Case Study of Youtz Community Hub - Azizah, Fathiyyah; Tri Lestari, Martha (Universitas Semarang, 2025)
Purpose: This study aims to analyze communication strategies in empowering online communities for the development of digital social innovation through Youtz Community Hub. This study was conducted to determine how communication strategies can support community empowerment and encourage the creation of social innovation in the digital era. Methods: This study uses a qualitative approach with a case study method. Data collection was conducted through in-depth interviews and participant observation of programs implemented by Youtz Community Hub. This is because the community has an interesting communication strategy in empowering the community online. The focus of this study includes five stages of communication strategy, namely analysis and research, policy formulation, program planning, communication implementation, and evaluation and feedback. Findings: The results of the study show that the digital communication strategy implemented, especially through social media, can increase participation, involvement, and the impact of community empowerment. This strategy is also effective in encouraging social innovation and building a collaborative ecosystem between communities, institutions, and other stakeholders. Originality: The novelty of this research lies in the participatory and data-driven digital communication approach applied in the context of online community empowerment. What sets this study apart is the integration of qualitative analysis tools, particularly Atlas.ti, to systematically code, visualize, and interpret narrative interview data and observational findings. These findings contribute to the advancement of inclusive and sustainable communication strategies in the digital era, particularly in digitally native youth communities.